1989
DOI: 10.1109/14.90284
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of miniaturized electrets

Abstract: This paper describes the realization process of small-size electrets by using techniques generally applied in the fabrication of integrated circuits and microsensors. In the first part of the paper, attention is paid to the different electret decay mechanisms and their relative contribution to the overall stability of miniaturized electrets. Then, a process is described by which polymer electrets such as Teflon-FEP and PTFE can be deposited and shaped in a predefined pattern on a silicon wafer. In the third pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…The potentials V, are normalized to their initial potential Knit right after the thermal treatment, as mentioned in Section 3. The conclusions of our earlier paper [7] are consolidated by the recent measurements. The electric field of the electret, charged to 663 V, amounts to 6 MV/cm, which is very close to the reported theoretical maximum field strength of 7 MV/cm [lo].…”
Section: Time [Day]mentioning
confidence: 70%
See 3 more Smart Citations
“…The potentials V, are normalized to their initial potential Knit right after the thermal treatment, as mentioned in Section 3. The conclusions of our earlier paper [7] are consolidated by the recent measurements. The electric field of the electret, charged to 663 V, amounts to 6 MV/cm, which is very close to the reported theoretical maximum field strength of 7 MV/cm [lo].…”
Section: Time [Day]mentioning
confidence: 70%
“…From the results of experiments, described in our previous paper [7] concerning Si02 electrets, it was concluded that the cancellation of lateral surface conduction would result in prolonged charge retention. Because the silanol groups at a Si02 surface were reported either to be the cause of the conductivity due to mobile protons of those groups or to attract, by their polar nature, physically absorbable water molecules, it was thought and shown that substitution of these surface groups sufficiently reduced the surface conductivity, according to the following mechanism.…”
Section: Charge Decaymentioning
confidence: 99%
See 2 more Smart Citations
“…C Electrets are materials that provide a semipermanent electric potential. While the first electret was discovered by the polarization of carnauba wax, 1 a wide variety of organic [2][3][4][5][6] and inorganic 7,8 dielectric materials have since been used as electret materials and their charging mechanisms have been investigated as well. 9,10 However, applications of electret films seem to be quite limited, especially in the area of microdevices; only electret condenser microphones are commercially available at the present time.…”
mentioning
confidence: 99%